Analisis Pengaruh Pandemi Covid-19 terhadap Pertumbuhan Ekonomi dengan Uji Statistik Mc Nemar - Oeliestina, Oeliestina (Jurnal Paradigma Ekonomika, 2021)
The COVID-19 pandemic has affected the social, political sector and almost paralyzed the economic sector. In the second quarter of 2020, modern countries such as America, Singapore, Germany, France, and Italy have entered a recession. Many countries' economic growth has contracted due to the influence of restrictions on human movement. This study will examine the impact of the COVID-19 pandemic on Indonesia's national economy. Using Mc Nemar's test statistics shows whether the COVID-19 pandemic is affecting the Indonesian economy, especially the economy of 34 provinces. Statistical tests will also be used to see the effect of the COVID-19 pandemic on 17 categories in the GRDP of the Business Field. The study concludes from the results of Mc Nemar's statistical test that the COVID-19 pandemic affects the Indonesian economy and the economy of 34 provinces with a significance result of less than 0.05. Mc Nemar's statistical test also proved that 17 categories/sectors were affected due to the covid pandemic (significance below 0.05). Meanwhile, the sectors most severely affected are transportation, provision of accommodation and food and drink, company services, and other services. These four sectors had economic growth rates contracted to double digits when entering the second quarter of 2020. Â  Â